SIGNIFIKANSI TARIKH CIPTA DAN TERBIT DALAM PEMBACAAN TEKS - Nugraha, Dipa (JURNAL SKRIPTA, 2025)
This article discusses the important status of the time of creation and or publication of literary works in interpretation. This type of article is a literature review article. The sample cases of literary studies used are the cases of Serat Darmogandul, the novel Sitti Nurbaya, the poem "Diponegoro," and the novels of Iwan Simatupang. Literature reviews are applied to the cases presented so as to lead to a theoretical concept regarding interpretations that do not deviate far from the text when the date of creation and or publication coincide. It can be concluded that the function of the date of creation and or year of publication of a text in the study of literary texts, namely: 1.) providing a basis for expectations and anticipation, 2.) providing a foothold for tracing changes in the text, 3.) the time of creation of the text provides clarity regarding the position of the text in the universe-chronicle which is part of its existence, and 4.) helping determine the position of a text in the historical timeline among other texts.